Engaging future professionals in the promotion of active offer for a culturally and linguistically appropriate system - Bouchard, Pier; Vézina, Sylvain; Cormier, Manon; Laforge, Marie-Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, the authors examine the approach of the Consortium national de formation en santé (CNFS) in the area of the active offer of health care and social services in French, in light of ideas from strategic analysis. We will look at the steps the CNFS has taken with regard to a consortium of Francophone post-secondary institutions offering programs in the area of health and social services, to design and share resources to prepare Francophone professionals to take up the challenge of improving access to French-language services in minority settings. In response to a recommendation made in an evaluation report in 2008, the CNFS has undertaken a process to prepare graduates of its post-secondary programs to become ambassadors who are prepared to improve access to safe, quality services for Francophone communities in minority settings. Readers will learn about an actor-centred strategy enabling professionals to provide active offer of services in French. Readers will also learn about the series of challenges, issues, and ideas for action that occur as resources are developed. Because the process is dynamic we conclude by introducing some of the measures now being developed or implemented. Key Words: language and health, issues and challenges of active offer, quality and safety of care, actor, strategy, commitment, education and training.

L’engagement des futurs professionnels en faveur de l’offre active et d’un système adapté linguistiquement et culturellement - Bouchard, Pier; Vézina, Sylvain; Cormier, Manon; Laforge, Marie-Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, les auteurs proposent de revisiter, à la lumière des propositions de l’analyse stratégique, la démarche empruntée par le Consortium national de formation en santé (CNFS) en matière d’offre active de services sociaux et de santé en français. Le CNFS étant un consortium d’établissements de formation postsecondaire francophones offrant des programmes dans le domaine de la santé et des services sociaux, il sera question de suivre son parcours vers la conception et la transmission d’outils pour préparer les professionnels francophones à relever les défis relatifs à l’accès aux ser vices en français en contexte minoritaire. Nous y verrons comment, en réponse à une recommandation contenue dans un rapport d’évaluation datant de 2008, le CNFS a entrepris une démarche pour faire en sorte que les diplômés issus des programmes qu’il soutient deviennent des ambassadeurs capables d’intervenir pour un meilleur accès à des services de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire. Le lecteur y découvrira une stratégie axée sur l’acteur selon laquelle un professionnel sensibilisé et outillé serait en mesure d’influencer le système pour améliorer l'offre active de services en français. Il y fera également le constat d’une série de défis, d’enjeux et de pistes d’action qui se sont profilés tout au long de la démarche. Le processus étant dynamique, nous conclurons en présentant quelques mesures en cours d’élaboration ou d’implantation. Mots-clés : langue et santé, enjeux et défis de l’offre active, qualité et sécurité des soins, acteur, stratégie, engagement et formation.

Rapport du dialogue sur l’engagement des étudiants et des futurs professionnels pour de meilleurs services de santé en français dans un contexte minoritaire - Bouchard, Pier; Vézina, Sylvain; Savoie, Mylène (Consortium national de formation en santé, 2010)

Programme de formation clinique dans les communautés francophones en situation minoritaire du Consortium national de formation en santé - Volet La Cité - Boulet, Mélanie (Reflets, 2018)

La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

French-language health care services in Ontario - Deroche, Francine. C. M. (Healthcare Management Forum, 1994)
The French Language Services Act, 1986 has had an impact on the provision of health care services in Ontario. The Ontario Ministry of Health's implementation of French-language services is examined in light of three criteria: permanency, quality and accessibility of services. Issues are raised around the measurement and creation of demand for services; the health human resources shortage; health care priorities; what constitutes a high quality service; and the influence of the political and economic climates. The continuing challenge is to provide permanent and accessible high quality French-language health care services within an ailing health care system.

Exploration of English language program undergraduate nursing students’ attitudes toward the risks of English-French language discordance and their implementation of the active offer of French language health services in Ontario [master's thesis, University of Ottawa] - Ford, Amy (University of Ottawa, 2018)
As has been reported in Canadian research on the experiences of Francophone patients and Francophone health professionals, active offer is not common or well performed in the Ontario healthcare system (Bernier, 2009; Boileau, 2016; Bouchard & Desmeules, 2013; Drolet et al., 2014; Hien & Lafontant, 2013). This descriptive quantitative research explored the self-reported awareness and implementation of the active offer concept during clinical placements by English language program 4th year undergraduate nursing students. A total of 69 participants were recruited in April 2017 to complete a paper or online-based survey. The survey consisted of questions on French language abilities, awareness of the patient safety risk of language discordance, communication experiences with Francophone patients and opinions of the role of the nurse, healthcare organizations and universities in the implementation of active offer. The participating nursing students reported little knowledge and training for implementing active offer during clinical settings. Despite the lack of preparation, the majority of them (92%) reported caring for a Francophone patient at least once with 25% doing that eight times or more during their clinical placements. More than 84% reported finding a way to communicate with Francophone patients in French, by speaking to them in French themselves or by asking Francophone colleagues, a professional interpreter or the patients’ family to interpret for them. Study recommendations include training nursing students during their undergraduate studies about the patient safety risks of language discordance, active offer and how to implement it. All English program nursing students should also be taught how to access and work with a professional interpreter. Those with French language skills should be encouraged to take healthcare specific language training. New research should be done to explore communication between English language program nursing students and Francophone patients to identify if it is safe and adequate from both the student and the patient’s point of view.

L’offre de services de santé en français en contexte francophone minoritaire - Forgues, Éric; Bahi, Boniface; Michaud, Jacques; Deveau, Kenneth; Boudreau, Jonathan; St-Onge, Sylvain (Institut canadien de recherche sur les minorités linguistiques, 2011)

Une formation en service social à distance en français : le modèle de l’Université Laurentienne - Garceau, Marie-Luce; Marcoci, Gabriela (Reflets, 2015)

Le rôle de l’hôpital communautaire Montfort comme pilier francophone de formation - Joanisse, Dr. John (Reflets, 2002)

Recherche-graphie: Des stages en français pour se préparer à travailler auprès communautés francophones en situation minoritaire - Landry, Simon (Evidence Exchange Network (EENet), Programme de soutien au système provincial (PSSP) au Centre de santé mentale et de toxicomanie (CAMH))
Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire, des stages en milieu francophone ont été offerts à des étudiant.e.s bilingues des universités anglophones. De tels stages pourraient encourager ces nouveaux professionnels en santé à s’afficher comme pouvant s’exprimer enfran çais, même quand ils-elles se trouvent à travailler dans un milieu anglophone.

Rapport de l’évaluation sommative du Projet de formation et de recherche du Consortium national de formation en santé - LeBlanc, Pierre (Conseillers en gestion PRAXIS, 2008)

HR Support Kit – Pathway to Bilingual services - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Trousse d’appui RH – Vers un service bilingue - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

L’offre active des services de santé en français : pourquoi et comment la mettre en pratique - Réseau du mieux-être francophone du Nord de l’Ontario
Réseau du mieux-être francophone du Nord de l’Ontario offre une formation sur l'offre active, disponible en français et en anglais, qui s’adresse à toute personne qui travaille ou qui étudie dans le domaine de la santé ou dans un domaine connexe.

Pratique # 16 : Des stages en français pour préparer à servir la clientèle francophone en milieu francophone minoritaire (Ontario) - Savard, Jacinthe; Benoît, Josée (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Le projet avait pour but de fournir des opportunités de stages cliniques en français aux étudiant·es francophones ou francophiles, inscrits dans des programmes de formation aux professions de la réadaptation offerts en anglais dans les universités canadiennes hors Québec. Les objectifs pour les stagiaires, les avantages pour les organismes qui les accueillent, ainsi que les étapes de préparation de ces stages sont décrits.

Des stages en français pour se préparer à travailler auprès communautés francophones en situation minoritaire - Savard, Jacinthe; Benoît, Josée; Dubouloz, Claire-Jehanne; Breau-Godwin, Stéphanie (Reflets, 2018)
Dans l’objectif d’augmenter le nombre de professionnelles et professionnels pouvant offrir des services sociaux et de santé en français dans les communautés francophones en situation minoritaire (CFSM), des stages en français ont été offerts à des étudiantes et étudiants bilingues de programmes de formation professionnelle offerts en anglais au sein d’universités canadiennes. L’expérience a été positive pour l’ensemble des parties prenantes : stagiaires, éducatrices-cliniciennes et responsables de la formation clinique. Après cette expérience, les stagiaires ont mentionné avoir une meilleure connaissance des défis d’accès aux services rencontrés par les CFSM et se sentir plus en mesure d’offrir des services en français à ces communautés. Mots-clés : stage en français, formation clinique, communautés francophones en situation minoritaire, offre active, réadaptation

Évaluation métrologique de la Mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Benoît, Josée; Bouchard, Pier (Reflets, 2014)
Comment peut-on mesurer l’impact des actions entreprises pour améliorer l’offre active de services sociaux et de santé en français dans les communautés francophones en situation minoritaire? Un questionnaire mesurant premièrement les comportements individuels de l’offre active et deuxièmement la perception du soutien organisationnel à faire de l’offre active a été créé. La validité de contenu de la Mesure de l’offre active de services en françaisen contexte minoritaire a été établie à l’aide d’une recension d’écrits, de consultations menées auprès d’expertes et d’experts et d’un sondage Delphi pancanadien. Sa fidélité a été examinée à partir de données recueillies auprès de récents diplômés en santé et en service social. L’outil démontre une bonne consistance interne et des études auprès d’un plus large échantillon sont nécessaires pour augmenter la confiance envers sa stabilité temporelle. Il s’agit des premiers pas d’une démarche visant à mesurer l’évolution des comportements d’offre active à la suite d’activités de formation ou de changements organisationnels en faveur de services en français. Une telle mesure est aussi susceptible d’être utile dans les recherches visant à saisir les déterminants de ces comportements d’offre active. Mots-clés : Offre active de services en français, formation des professionnelles ou professionnels en santé et services sociaux, soutien organisationnel, évaluation, minorité, langue et services, qualité des soins et services, sécurité des clientes ou clients/patientes ou patients

Adopting a lay navigator training programme in primary care - Toal-Sullivan, Darene; Lemonde, Manon; Gauthier, Alain P.; Dahrouge, Simone (Health Education Journal, 2021)
Introduction: There is growing interest in the role and use of patient navigators within the health care system. Currently, qualifications and training expectations documented in the literature vary tremendously depending on context and patient population. This paper details the theoretical and pedagogical principles used to develop, implement and evaluate a training programme for lay patient navigators working in a primary care setting. Methods: The planning process involved (a) conducting an educational needs assessment, (b) identifying the theory underpinning the curriculum, (c) developing learning objectives and teaching strategies, (d) formulating evaluation methods, (e) implementing the programme and (f) refining the curriculum based on evaluation feedback and lessons learned. The training programme was first implemented in May 2017 and has evolved over the past 3 years based on our observations and feedback from the programme participants. Results: The training programme involves a total of 25 hours of online and face-to-face education sessions, and ongoing community mentorship from experienced navigators. All training components are rooted in theoretical principles and proven pedagogical approaches. The knowledge, skills and abilities acquired are also tied to core competencies of the role of lay patient navigator. Conclusion: The development of this lay navigator training programme was carefully designed with evidence-based competencies and practical realities to ensure rigour in preparing and supporting navigators’ work in primary care settings.

Susciter chez les professionnels une prise de conscience critique des enjeux liés à la littératie en santé pour des francophones en situation de minorité linguistique en Ontario - Zanchetta, Margareth. S.; Maheu, C.; Fontaine, C.; Salvador-Watts, L.; Wong, N. (Maladies chroniques et blessures au Canada, 2014)

Awakening professionals’ critical awareness of health literacy issues within a francophone linguistic-minority population in Ontario - Zanchetta, Margareth Santos; Maheu, Christine; Fontaine, C.; Salvador-Watts, Liana; Wong, N. (Chronic Diseases and Injuries in Canada, 2014)